Credit Decisions Making Through the Use of Information Company’s Financial Performance and Environmental Performance - Putu Riesty Masdiantini; Ni Luh Asri Savitri; Sunitha Devi (Universitas Pendidikan Ganesha, 2023)
Before credit is given, the bank must first conduct a credit analysis to ensure that the customer can really be trusted. It is important for loan officers to understand other information or the latest information related to lending. Through the use of data on the company's financial performance and environmental performance, this study seeks to obtain empirical evidence about the provision of loan decisions. This study uses a quasi-experimental design with a 2X2 factorial layout, which is an experimental method. 81 students enrolled in the Bachelor of Accounting Program comprised the sample for this study, which was chosen using a purposive sampling technique and the non-probability method. The Two-Way Analysis of Variance (ANOVA) test was employed in the data analysis process. The study's findings show that credit decisions are significantly impacted by both financial and environmental performance.